Estudo da oxidação superficial de ligas odontológicas de Ni-Cr em plasma pulsado para uso em restaurações metalocerâmicas - Souza, Tatiana Oliveira de (2008)
Metal ceramic restorations matches aesthetic and strength, and in your making occurs an interface oxide layer, wetting resulting and atomic and ionic interactions resulting between metal, oxide and porcelain. However, frequent clinical fails occurs in this restoration type, because lost homogeneous deposition oxide layer and lost interface bond. Thus, in this study, thought depositate homogeneous oxide films above Ni-Cr samples surfaces polite previously, at plasma oxide environment. Six samples was oxided at 300 and 400ºC at one hour, and two samples was oxided in a comum chamber at 900ºC, and then were characterized: optical microscopic, electronic microscopic, micro hardness, and X ray difratometry. Colors stripes were observed at six samples plasma oxided and a grey surface those comum oxided, thus like: hardness increase, and several oxides from basic metals (Ni-Cr)